Obstetric Outcomes in Women With Early Bulky Cervical Cancer Downstaged by Neoadjuvant Chemotherapy to Allow for Fertility-Sparing Surgery: A Meta-analysis and Metaregression. Issue 4 (May 2018) - Laios, Alexandros; Kasius, Jenneke; Tranoulis, Anastasios; Gryparis, Alexandros; Ind, Thomas
Abstract : Objective: It is difficult to critically outline the optimal treatment for women with early-stage cervical cancer (eCC) wishing fertility preservation. Neoadjuvant chemotherapy (NAC) to downstage "bulky" eCC could potentially lead to fertility-sparing surgery (FSS) in a wider patient population. The rationale is to provide oncological safety balanced with maximal fertility effort. We aimed to obtain the most accurate fertility outcomes for eCC women treated with NAC followed by FSS and identify potential factors favoring fertility. Methods: A systematic search of MEDLINE, EMBASE, Web of Science, and Cochrane Database was performed. Studies that reported obstetric outcomes of eCC women treated with NAC followed by FSS were located. For the meta-analysis, we calculated the proportions of women who had the outcomes per total number of women who were considered for FSS. For the meta-regression, we extracted the relative risk of the outcome variables to enable comparison of the results across the studies. Results: Seven studies enrolling 86 patients were included in the meta-analysis. Pooling of results from seven studies rendered summary proportions of 0.49 (95% confidence interval [CI], 0.32–0.66) and 0.42 (95% CI, 0.32–0.53) for the outcomes of pregnancies and live births, respectively. The outcome of first- and second-trimester losses by pooling seven studies rendered a summary proportion of 0.16 (95% CI, 0.09–0.27). For the outcome of premature deliveries, pooling of results from five studies rendered a summary proportion of 0.06 (95% CI, 0.02–0.16). This reached 0.29 (95% CI, 0.15–0.48) in women who achieved live births. In multivariate meta-regression, the more radical surgical approach resulted in a less favorable pregnancy rate compared with the less radical surgical approach ( P = 0.015). Conclusions: This strategy achieves live births in four of 10 eCC women who desire fertility, whereas their risk of miscarriage is low. Three of 10 live births will be premature. Abstract : Supplemental digital content is available in the text.